Performance of COPD population screener questionnaire in COPD screening: a validation study and meta-analysis - Yanhui Gu; Ying Zhang; Qian Wen; Yao Ouyang; Yongchun Shen; He Yu; Chun Wan; Jing Zhu; Fuqiang Wen (Annals of Medicine)
This study aimed to validate the chronic obstructive pulmonary disease (COPD) Population Screener (COPD-PS) questionnaire as a screening tool in a cohort of Chinese subjects who underwent a health examination, and to summarise its overall performance through a meta-analysis. We enrolled 997 subjects aged ≥40 years who underwent a health examination, both lung function and COPD-PS data were collected. The screening performance of COPD-PS was evaluated with a receiver operating characteristic (ROC) curve analysis, using the area under the curve (AUC) to assess the screening accuracy. A standard diagnostic meta-analysis was used to summarise the screening performance of COPD-PS for COPD. Of the 997 subjects, 157 were identified as having COPD. The COPD-PS score was significantly higher in COPD patients than controls (5.03 ± 5.11 vs. 2.72 ± 1.80, p < .001). At a cut-off of 4, the sensitivity and specificity of COPD-PS for identifying COPD were 74.52 and 70.24%, respectively, with an AUC of 0.79. Eight studies (including this study) were included in this meta-analysis. The pooled estimates for COPD-PS were as follows: sensitivity of 0.66 (95% CI: 0.47–0.63), specificity of 0.86 (95% CI: 0.84–0.89), positive likelihood ratio of 3.00 (95% CI: 1.65–5.47), negative likelihood ratio of 0.43 (95% CI: 0.35–0.52) and diagnostic odds ratio of 7.24 (95% CI: 3.91–13.40). The AUC of the summary ROC curve was 0.78. COPD-PS appears to be a useful tool for screening individuals with a high risk of COPD and guiding the selection of individuals for subsequent spirometry examination.KEY MESSAGESCOPD-PS is a simple and useful method to screen COPD.The combination of COPD-PS with other tools may improve the screen performance.